2022
DOI: 10.1029/2022gl098577
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the January 2022 Tonga Volcanic Eruption on the Ionospheric Dynamo: ICON‐MIGHTI and Swarm Observations of Extreme Neutral Winds and Currents

Abstract: Isolated disturbances such as earthquakes, tsunamis, and solar eclipses, as well as explosions from volcanoes, nuclear detonations, and meteor air bursts can offer discrete tests for models of atmosphere-ionosphere coupling and variability (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 40 publications
6
89
1
5
Order By: Relevance
“…This was also reported in Harding et al. ( 2022 ) and agrees approximately with the timing of volcano‐induced atmospheric Lamb waves as they swept across the American sector. The zonal wavelength was estimated to be 3,500–4,500 km, assuming the wave does not change appreciably over the ∼10 min required for the satellite to traverse one wave cycle.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…This was also reported in Harding et al. ( 2022 ) and agrees approximately with the timing of volcano‐induced atmospheric Lamb waves as they swept across the American sector. The zonal wavelength was estimated to be 3,500–4,500 km, assuming the wave does not change appreciably over the ∼10 min required for the satellite to traverse one wave cycle.…”
Section: Resultssupporting
confidence: 89%
“…Harding et al. ( 2022 ) reported ICON‐MIGHTI wind measurements over two orbit passes and analyzed the dayside ionospheric dynamo response to the volcano eruption. Although Figures 2b and 2c have already shown dusktime wind measurements over a concentrated area, we extend this information by providing global wind measurements for six consecutive ICON‐MIGHTI orbits in order to comprehensively investigate the possible prolonged dynamic and electrodynamic effects of volcano‐induced waves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported considerable penetration electric field even without severe IMF B z fluctuations (e.g., D'Angelo et al, 2021;Piersanti et al, 2020). Harding et al (2022) proposed that if the penetration electric fields were the main cause of the EEJ variation, strong correlations between the IEF E y and DH would be expected. A correlation coefficient as high as 0.6 was observed in the Peru and Brazil sectors during the post-volcanic-eruption hours.…”
Section: Discussionmentioning
confidence: 96%